Slavery in the literature of Madagascar: The case of Raharimanana - (:unkn) unknown (My University, 2008)
"Although the question of slavery is often linked to the African continent, which paid a heavy tribute to the three-cornered trade, other pages should be recalled, in the Indian Ocean and beyond" Khal Torabully Africultures N°67, p.101. Madagascar is often said to be a digest of Africa and Asia. This is partly true as the first inhabitants of the island came from African and southeastern Asian coasts. But, this is also partly false as Madagascar doesn't look either like Africa, or like other islands of the Indian Ocean or any other place in the world. Many animal and vegetal endemic species live there. As far as the people of Madagascar is concerned, it is composed of a great number of ethnies such as the Merina and the Betsileo living on the High Plateau of the centre, the Sakalava and the Betsimisaraka on the coasts… But all theses ethnies are united by one common language : Malagasy. Could Madagascar avoid foreign predation thanks to its eccentred geographical situation? Unfortunately not. It had been a long time since Arab sailors knew the island which Marco Polo noticed on his way to China and which was officially " discovered " in 1500 by Portugese sailors, the first Europeans to land on the island. They call it Sao Lourenço. But the presence of European people won't last, except for a French trading post in Fort-Dauphin (in the South), maintained with great difficulty from 1643 to 1674. For its part, the Madagascan state forms itself progressively and in 1828 it is unified ; the first queen of Madagascar is named Ranavalona 1 st .
Keywords: African Research